Examining English Speaking Challenges and Evaluating the Effectiveness of Drama in Enhancing Speaking Skill - Eer Roviyanti; Harpain, Harpain (Jurnal Multidisiplin Indonesia, 2024)
This study examines students’ challenges in speaking English and evaluates the effectiveness of drama as a learning medium to improve speaking skills. A mixed-methods research design was employed, combining qualitative interviews and quantitative pretest and posttest assessments to measure the impact of drama-based learning. Conducted at SMA Al Azhar 3 Bandar Lampung, the research involved 20 students participating in drama sessions focused on monologue storytelling. The interviews revealed common difficulties such as pronunciation errors, grammatical issues, limited vocabulary, low self-confidence, and anxiety. Statistical analyses using SPSS confirmed normality in pretest and posttest data (p > 0.05) and showed a significant improvement in speaking skills after the intervention (Sig = 0.000, α = 0.05). A paired sample t-test indicated a mean difference (t-count = 11.856), surpassing the critical t-value (t-table = 2.093), supporting the alternative hypothesis (Ha). These findings highlight drama's effectiveness in enhancing students' speaking proficiency and contribute to the literature by demonstrating drama's potential in overcoming language learning challenges, offering valuable insights for educators.